Сучасні математичні моделі компенсації похибок інерціальних датчиків для застосування в експериментах по калібруванню - Хацько, Наталія Євгенівна (НТУ "ХПІ", 2017)
Розглядаються методи калібрування інерційних датчиків і математичні моделі компенсації їх помилок, що дозволяють ідентифікувати оцінки параметрів цих моделей при проведенні натурних експериментів з калібрування. Огляд проводиться за матеріалами останніх десяти років. Аналіз літератури привів до виділення універсальної математичної моделі, що використовується в більшості експериментів. Також виділені типові фактори, які зазвичай враховуються в побудові моделей і розробці планів експериментів. Отримані результати в подальшому можуть бути корисними для вибору доступного і припустимого методу калібрування окремого інерціального модуля.

In this paper some of the mathematical models applied for calibration of inertial sensors in the last decade are considered. The attention that has been received by the mathematical models of sensor errors is mainly due to the wide application of the method of algorithmic compensation of errors in the inertial system during its operation. As a whole, calibration is limited to estimating the key errors: scale factor, offset and misalignment of the sensor axes. In the paper several basic mathematical error models of gyroscopes and accelerometers are defined. The analysis of the literature made it possible to determine the factors that must be taken into account when developing mathematical models for sensors operating on different physical principles, and also led to the identification of a universal mathematical model used in the most experiments. The main result of this review is the understanding that individual calibration of sensors, even without using precision stands, can significantly increase the accuracy of the inertial unit and is an indispensable stage of operation, especially for mass production sensors. The obtained conclusions can be used in the future when choosing an available calibration method for an individual inertial module.
Modern mathematical models of error compensation for inertial sensor used in their calibration
Keywords: МЕМС-датчики; мікро-електро-механічні системи; безпілотні літальні апарати; бесплатформна інерціальна навігаційна система; фільтр Калмана; метод найменших квадратів; calibration of the inertial sensor; mathematical model of error compensation; zero drift; sensor axes misalignments